Smart Governance Dan Peran Digitalisasi Dalam Tata Kelola Pemerintahan: Sebuah Tinjauan Literatur - Mhd Farid Alamsyah; Dinda Yuvia Ibnayasha; Khairunnisa Nabilah; Boni Saputra; M. Fachri Adnan (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Modern governance faces transformative pressure from rapid digital technology development. Smart governance emerges as a new paradigm integrating digitalization into public administration to enhance efficiency, transparency, accountability, and citizen participation. This article aims to examine the role of digitalization in realizing smart governance and its implementation challenges, particularly in Indonesia. A literature review method was applied to 17 selected scientific sources published between 2019 and 2025, sourced from Scopus Q1–Q2 indexed journals and SINTA-accredited journals. Findings indicate that government digitalization significantly impacts bureaucratic performance, public trust, and civic participation, though success is largely determined by human resource readiness, digital leadership, and equitable infrastructure. In Indonesia, SPBE implementation, the LAPOR! platform, and SmartASN demonstrate digital transformation commitment, though the digital divide across regions remains a significant challenge.